Bio-pitch as a binder in carbon anodes for aluminum production: Bio-pitch properties and its interaction with coke particles. (1st September 2020) - Hussein, Asem; Lu, Ying; Mollaabbasi, Roozbeh; Tessier, Jayson; Alamdari, Houshang
Abstract: Aluminium industry depends today on only the coal-tar-pitch as a binder to produce carbon anodes. However, it becomes difficult to secure a high-quality binder for the future needs of the aluminum industry as coal-tar-pitch is a non-renewable fossil binder. In this work bio-pitch, as a renewable and environmentally friendly binder, was produced by the heat treatment of a bio-oil. The range of heat treatment temperature and heating rate was selected to achieve the desired physical properties of the produced bio-pitch. This bio-pitch showed a softening point and a viscosity similar to that of the coal-tar-pitch. In addition, it was able to cover and spread over the coke particles and further, penetrate into their open pores. According to the results of this work, the bio-pitch is a promising candidate to replace the coal-tar-pitch to produce a homogenous and mechanically stable green carbon anode.